2020
DOI: 10.1016/j.phrs.2020.105127
|View full text |Cite
|
Sign up to set email alerts
|

Hanshiyi Formula, a medicine for Sars-CoV2 infection in China, reduced the proportion of mild and moderate COVID-19 patients turning to severe status: A cohort study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
0
37
0
2
Order By: Relevance
“… Author, year Method Inclusion criteria Number of patients Basic treatment Traditional Chinese Medicine Outcome Gender (Male/Female) Age (years) Comorbidity Initial symptoms Jie Zhao, 2020 [ 58 ] Randomized controlled trial Patients with severe COVID-19 39 (WM group 24, TCM and WM group 15) Bed rest and adjuvant therapy; ensure adequate calorie and water intake; maintain water and electrolyte balance and homeostasis and strengthen psychological treatment for older children when necessary. Yidu-toxicity blocking lung decoction (Bitter almonds, raw gypsum, trichosanthes, raw rhubarb, raw ephedra, roasted ephedra, Tinglizi, peach kernel, grass fruit, betel nut, atractylodes), 2 weeks White blood cell count, neutrophil count, lymphocyte count, IL-6, IL-8, IL-2R, TNF-α, C-reactive protein, immune function, cure rate, length of hospital stays 22/17 Fever (94.87 %); dry cough (79.49 %) Jiaxing Tian, 2020 [ 60 ] Retrospective cohort trial Mild, moderate COVID-19, HSYF in the exposed group used for more than 2 days 721 (exposed group 430, non-exposed group 291) Treatment Guideline for COVID-19 released by the National Health Commission of the People’s Republic of China HSYF (Ephedra, Gypsum, Almond, Qianghuo, Tinglizi, Guanzhong, Earth Dragon, Xu Changqing, Huoxiang, Peilan, Cangzhu, Yunling, Raw Atractylodes, Jiao Hawthorn, Jiao Shenqu, Jiao Malt, Magnolia, Jiao Betel Nut, Simmering Grass Fruit, ginger) Proportion of mild and moderate COVID-19 patients who progressed to severe disease 347/374 48 Hypertension (16.9 %), fatty liver (7.9 %), diabetes (7.1 %) Fever (51.2 %), cough (27.6 %), diarrhea (20.8 %), fatigue (19.0%) Mingzhong Xiao, 2020 [ 56 ] Randomized controlled trial Suspicious and confirmed COVID-19 cases; 18−85 years old, regardless of gender; provide informed consent 283 (LHQWC 94, HXZQG + LHQC 95, WM 94) …”
Section: Obvious Advantages Of Tcm For the Treatment Of Covid-19: Dirmentioning
confidence: 99%
See 1 more Smart Citation
“… Author, year Method Inclusion criteria Number of patients Basic treatment Traditional Chinese Medicine Outcome Gender (Male/Female) Age (years) Comorbidity Initial symptoms Jie Zhao, 2020 [ 58 ] Randomized controlled trial Patients with severe COVID-19 39 (WM group 24, TCM and WM group 15) Bed rest and adjuvant therapy; ensure adequate calorie and water intake; maintain water and electrolyte balance and homeostasis and strengthen psychological treatment for older children when necessary. Yidu-toxicity blocking lung decoction (Bitter almonds, raw gypsum, trichosanthes, raw rhubarb, raw ephedra, roasted ephedra, Tinglizi, peach kernel, grass fruit, betel nut, atractylodes), 2 weeks White blood cell count, neutrophil count, lymphocyte count, IL-6, IL-8, IL-2R, TNF-α, C-reactive protein, immune function, cure rate, length of hospital stays 22/17 Fever (94.87 %); dry cough (79.49 %) Jiaxing Tian, 2020 [ 60 ] Retrospective cohort trial Mild, moderate COVID-19, HSYF in the exposed group used for more than 2 days 721 (exposed group 430, non-exposed group 291) Treatment Guideline for COVID-19 released by the National Health Commission of the People’s Republic of China HSYF (Ephedra, Gypsum, Almond, Qianghuo, Tinglizi, Guanzhong, Earth Dragon, Xu Changqing, Huoxiang, Peilan, Cangzhu, Yunling, Raw Atractylodes, Jiao Hawthorn, Jiao Shenqu, Jiao Malt, Magnolia, Jiao Betel Nut, Simmering Grass Fruit, ginger) Proportion of mild and moderate COVID-19 patients who progressed to severe disease 347/374 48 Hypertension (16.9 %), fatty liver (7.9 %), diabetes (7.1 %) Fever (51.2 %), cough (27.6 %), diarrhea (20.8 %), fatigue (19.0%) Mingzhong Xiao, 2020 [ 56 ] Randomized controlled trial Suspicious and confirmed COVID-19 cases; 18−85 years old, regardless of gender; provide informed consent 283 (LHQWC 94, HXZQG + LHQC 95, WM 94) …”
Section: Obvious Advantages Of Tcm For the Treatment Of Covid-19: Dirmentioning
confidence: 99%
“…The difference was statistically significant. After considering gender and age using stratified analysis and propensity score matching, the difference in the aggravation rate between the HSYF and control group remained statistically significant [ 60 ].…”
Section: Obvious Advantages Of Tcm For the Treatment Of Covid-19: Dirmentioning
confidence: 99%
“…Because of the rapid advancement of science and technology, the research on TCMs continues to deepen. Previous preclinical and clinical findings have revealed that free TCMs can play an essential role in treating the pathophysiology of many diseases, including cancer (Wang R. et al, 2020), diabetes , Alzheimer's disease , depression (Zhu et al, 2020), and COVID-19 (Pan et al, 2020;Tian J. et al, 2020). In addition, some researchers have begun to focus their study on how to treat CNS injuries more effectively by using exosomes as drug delivery vehicles, these carrying TCMs to specific areas and exerting therapeutic effects.…”
Section: Exosomes As Drug Delivery Vehicles For Traditional Chinese Medicines (Tcms)mentioning
confidence: 99%
“…Koehne., and Atractylodes macrocephala Koidz.) can improve clinical symptoms, such as fatigue, cough, and fever, reduce the usage rate of antibiotics, and prevent the progression to severe COVID-19 (Xiao et al, 2020a;Tian et al, 2020;Xia et al, 2021). Currently, canti-COVID-19 agents mainly target SARS-CoV-2 spike receptor-binding domain or ACE2 enzyme activity to block the entry of COVID-19 to the cells.…”
Section: Viral and Bacterial Infectionsmentioning
confidence: 99%